CULTIVATING WELL-BEING: MARKET STRATEGIES FOR NUTRITIONAL IMPROVEMENT AMONG UGANDA’S MAIZE FARMERS - Mwesigwa, Henry Kizito; Bwanika, Julia Nantale (Ayden Journal of Management and Social Sciences, 2024)
Rural households rely on diverse livelihood strategies, including agriculture, agro-processing, trading, and off-farm activities, to meet their food and income needs. Integrating these households into market systems has brought about notable improvements in income levels, living standards, and poverty reduction. However, despite their indispensable contributions to household nutrition and food security, women's roles remain largely unrecognized and undervalued. This review examines the evolving landscape of rural livelihoods and market integration, highlighting the transformative effects on household well-being. It also sheds light on the often overlooked but critical role of women in ensuring food security and nutrition within rural households, underscoring the need for gender-responsive interventions to harness their full potential in sustainable development efforts.